Thinking with theory in qualitative research - Jackson, Alecia Youngblood 1968-; Mazzei, Lisa A. (Routledge, 2023)
Thinking with Theory in Qualitative Research: Second Edition demonstrates how to enact various philosophical concepts in practices of inquiry, effectively opening up the process of thought in qualitative studies.